The influence of glove and hand position on pressure over the ulnar nerve during cycling - Slane, J.; Timmerman, M.; Ploeg, H. L.; Thelen, D. G. (Clinical Biomechanics, 2011)
Chronic ulnar nerve compression is believed to be the primary cause of sensory and motor impairments of the hand in cyclists, a condition termed Cyclist's Palsy. The purpose of this study was to quantitatively evaluate the effects that hand position and glove type can have on pressure over the ulnar nerve, specifically in the hypothenar region of the hand. Methods